EFFECT OF INSULIN ADMINISTRATION DURING LUTEAL PHASE ON PROGESTERONE PROFILE AND CONCEPTION RATE IN BUFFALOES (BUBALUS BUBALIS)
The present study was conducted to test the effect of insulin administration (Human Mixtard®, S/C@ 0.25 IU/kg body weight